Analisis Potensi Lahan Padi Sawah di Kabupaten Majalengka Provinsi Jawa Barat - Yentri, Vivi Febrida, Ir. H.Taryono,M.Si (2016)
Index potential of land is appropriate assessment effort land land potential. Index agricultural potential is an important data which can be used to provide information on the evaluation and potential agricultural lands to be able to use the land optimally. This study aimed to analyze the distribution of land potential index in Majalengka, analyze the potential spread of wetland based on the index value the potential of land in Majalengka, and analyze the suitability of potential wetland and rice productivity in Majalengka. The method used in this research is the analysis of GIS through a tiered quantitative approach to land potential index 5 parameters, ie slope, lithology, rock type, hydrology, and prone to flooding as a limiting factor. Results obtained land potential index Majalengka divided into five classes, is very low of 100.33 km2 (7.58%); low-class area of 164.73 km2 (12.44%); the middle area of 376.4 km2 (30.66%); high-class area of 302.98 km2 (27.41%); and very high class area of 260.18 km2 (21.91%). Wetland has a very low potential area contained in district Sindangwangi. Potential low wetland contained in the district Leuwimunding and sub-district Malausma. Potential wetland is being contained in the District Ligung, Dawuan, Palasah, Sumberjaya, Kasokandel, Cigasong, Sindang, Rajagaluh, Bantarujeg, Banjaran, Talaga, Cikijing, and Cingambul. Potential high wetland contained in District Lemahsugih, Maja, Argapura, Majalengka, Panyingkiran, Kadipaten, and Sukahaji. Very high potential paddy fields are in District Kertajati and Jatitujuh. Correspondence between the land potential productivity of lowland rice paddies in Majalengka dominated not suite. The potential of wet land with paddy rice productivity suite contained in 6 sub-districts Kadipaten, Panyingkiran, Sukahaji, umberjaya, Sindangwangi, and Talaga. Keywords: Potential Land, Rice, Rice Productivity